Model for the combined effects of temperature, pH, and sodium lactate on growth rates of Listeria innocua in broth and Bologna-type sausages. - Houtsma, P C (1996)
A modified Monod equation was successfully applied to describe the maximum specific growth rate of Listeria innocua in a broth model in the presence of various concentrations of sodium lactate or NaCl. The combined effects of temperature and pH were assessed by translating the parameters of the modified Monod equation mu(m), alpha, and p') as functions of pH and/or temperature. As a result, the area in which the growth rate could be predicted was extended to include as a variable not only the salt concentration but also pH and temperature. The number of parameters needed to describe the experimental data was thereby reduced from 48 to 4 (NaCl) and from 42 to 5 (sodium lactate). The decline in the goodness of fit that accompanied the reduction in the number of parameters was within statistically acceptable ranges. The resulting model was compared with a polynomial fit, and it was proposed that the former was more suitable for the purpose of this study. The broth model for sodium lactate was evaluated with Bologna-type sausages. Because of the "worst-case" design of the broth model, it was necessary to reestimate one or all parameters to obtain a good description of the growth rate of L. innocua in the meat product. However, the simplicity of the model and the practical usefulness of its parameters offer considerable prospects for its use in predictive microbiology.